Introduction to colloid and surface chemistry - Shaw, Duncan J. (Oxford ; Boston : Butterworth-Heinemann, 1992)
This thoroughly updated edition continues to provide a concise overall coverage of colloid and surface chemistry, intermediate between the brief accounts in physical chemistry textbooks and the comprehensive coverage in specialized treatises. New information is included on the composition and structure of solid surfaces, dynamic light scattering, micro emulsions and colloid stability control. The book provides a sound, but easy to follow theoretical framework. It outlines relevant research techniques and considers technological applications. A basic knowledge of the principles of physical chemistry is assumed. It will appeal to a wide readership, both undergraduate and postgraduate students at universities and colleges of technology as well as scientists in industry who need a broad background in the subject.
Includes bibliographical references (p. 290-297) and index.
Keywords: Colloids; Surface chemistry; Electronic books